2017
DOI: 10.3329/jom.v18i1.31170
|View full text |Cite
|
Sign up to set email alerts
|

Non-Compliance to Doctors’ Advices among Patients Suffering from Various Diseases: Patients’ Perspectives: A Neglected Issue

Abstract: Abstract Abstract Abstract Backgr Backgr Backgr Backgr Background: ound: ound: ound: ound: An acknowledgement of the patient's perspectives about compliance towards doctors' advices is critical in ensuring better results of medical consultation. The compliance to therapies is a primary determinant of treatment success.The authors found a serious dearth of research on this issue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Studies have indicated inadequate education among patients using hospital systems and the continuum of care [ 33 ]. Over 45% of individuals utilizing healthcare systems struggle to navigate the continuum of care, with this percentage increasing when dealing with insurance or healthcare-associated costs [ 34 ]. Furthermore, over 55% of minorities, elderly individuals, and those with low socioeconomic status face difficulties in navigating the continuum of care due to factors such as lack of a permanent home or access to resources like a telephone or car [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have indicated inadequate education among patients using hospital systems and the continuum of care [ 33 ]. Over 45% of individuals utilizing healthcare systems struggle to navigate the continuum of care, with this percentage increasing when dealing with insurance or healthcare-associated costs [ 34 ]. Furthermore, over 55% of minorities, elderly individuals, and those with low socioeconomic status face difficulties in navigating the continuum of care due to factors such as lack of a permanent home or access to resources like a telephone or car [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Over 45% of individuals utilizing healthcare systems struggle to navigate the continuum of care, with this percentage increasing when dealing with insurance or healthcare-associated costs [ 34 ]. Furthermore, over 55% of minorities, elderly individuals, and those with low socioeconomic status face difficulties in navigating the continuum of care due to factors such as lack of a permanent home or access to resources like a telephone or car [ 34 ]. If patients had a better understanding of the roles of inpatient and outpatient therapies and how to navigate the confusing environment in regard to health insurance, resources, and patient-directed management, we might see a reduction in not only the overwhelming burden of hospitalizations, but also in the prevalence of conditions which prompt these visits.…”
Section: Discussionmentioning
confidence: 99%
“…Characteristics of therapeutic regimens varied, including administration routes, regimen complexity, treatment duration, and side effects. Patients are more likely to comply with treatment when given medications that can be taken easily (such as oral medications) (Jin et al, 2008 ; Memon et al, 2017 ). Complex treatments are thought to jeopardize patient compliance.…”
Section: Concept Analysis Of Patient Compliancementioning
confidence: 99%
“…Another good example is compliance in the medical world, where much attention has gone out to whether patients comply with doctors' orders (Memon et al 2017;Jin et al 2008;Reardon et al 2011;Costa et al 2015) and whether medical workers comply with hygiene norms (Erasmus et al 2010;Labrague et al 2018;Gammon et al 2008). Compliance in health has also focused on how government and the private sector can nudge individuals to be healthier through various compliance schemes (Bachireddy et al 2019).…”
mentioning
confidence: 99%